Aerobic Biodegradation of Chlorinated Hydrocarbons by Bacillus circulans WZ-12 CCTCC M 207006 under Saline Conditions - 於建明 蔡文吉 赵士良 王艳 陈建孟 (Chinese journal of chemical engineering, 2013)
A novel saline-tolerant bacterium Bacillus circulans WZ-12 was evaluated for its potential to degrade four chlorinated hydrocarbons under saline conditions. CHECl2 was effectively degraded by Bacillus circulans WZ-12 cells in the medium containing NaCl concentrations ranging from 5 g.L^-1 to 10 g-L^-1, and the maximum degradation efficiency （85%） was achieved at NaCl concentration of 10 g.L^-1. Similarly, Bacillus circulans WZ-12 was able to degrade CH2BrCl, C2H4Cl2, and C2H2Cl2 in the presence of 10 g NaCl per liter within 24 h. Cells of Bacillus circulans WZ-12 grown in minimal salt medium contained low levels of glycine betaine （GB）, but GB levels were 3- to 5-fold higher in cells grown in media with high salt. Kinetic analysis revealed that biodegradation of the four chlorinated hydrocarbons was concentration dependent and a linear inverse correlation （R2= 0.85-0.94） was observed between the rate of biodegradation （V） and salt concentration from 5 g.L〈 to 60 g.L-1. The growing cells （in minimal salt medium） degraded approximately 50% of the CH2C12 within 24 h, whereas the resting cells （in physiological saline） degraded only 25% of the CH2C12 within 24 h and were inactive after 36 h cultivation. Biodegradation could be repeatedly performed for more than 192 h with more than 50% removal efficiency. Bacillus circulans WZ-12 grows well in an aqueous/oil system, hence, it is effective for the treatment of industriai efflu- ents that contain chlorinated hydrocarbons with high salt concentrations.